Differential effects of plant protein ratio on renal function and mortality across CKD stages - Wang, Guoyi; Yi, Qiong; Zhang, Xueqin; Zhou, Min; Zhao, Jinwen; Lu, Haiyuan; Li, Ju; Meng, Deqian; Xu, Yong; Wang, Kai (Frontiers in Nutrition, 2025)
BackgroundWhile plant protein has been suggested to offer renoprotective benefits, the optimal proportion of dietary plant protein and its relationship with outcomes across different stages of chronic kidney disease (CKD) remains unclear.MethodsUsing data from the National Health and Nutrition Examination Survey (NHANES), we examined the association between plant protein ratio and estimated glomerular filtration rate (eGFR) across CKD stages. Plant protein ratio was categorized as low (< 33%), medium (33%–66%), and high (≥ 66%). Multiple imputation was performed for missing data. Weighted linear regression models were used to analyze plant protein ratio-eGFR associations, while Cox proportional hazards models assessed mortality risk. Dose-response relationships were evaluated using restricted cubic splines.ResultsAmong 16,163 participants, distinct patterns emerged across CKD stages. In Non-CKD, high plant protein ratio was associated with significantly higher eGFR compared to low plant protein ratio (β = 0.790, P = 0.039). In CKD G4, medium plant protein ratio showed significantly higher eGFR (β = 1.791, P = 0.025) compared to low plant protein ratio. For mortality risk, CKD G3 patients with medium plant protein ratio demonstrated significantly lower risk (HR = 0.67, 95% CI: 0.44–1.00, P = 0.047) compared to low plant protein ratio. Dose-response analyses revealed stage-specific patterns: U-shaped relationships in early CKD, transitioning to inverted U-shaped and J-shaped patterns in advanced stages.ConclusionThe association between plant protein ratio and outcomes varies across CKD stages, suggesting the need for stage-specific dietary recommendations. While moderate plant protein intake might be beneficial in early CKD, our findings in advanced stages were largely non-significant and require confirmation in larger studies before clinical recommendations can be made. These findings support a more nuanced approach to dietary protein source management in CKD, though further prospective studies are needed to confirm these associations.